Development of cotton variety IAPAR 4 - Paraná 1 - Pires, José Ricoy; Scott, Carlos A.; Ruano, Onaur; Yamaoka, Ruy Seiji; Turkiewicz, Luiz; Costa, Antonio; Almeida, Wilson Paes de; Marur, Celso Jamil; Santos, Walter Jorge dos (Pesquisa Agropecuaria Brasileira, 2014)
Data from 46 field experiments carried out during six years in the State of Paraná, with tine PR 4139, originated from individual selection in Reba B-50 variety, are presented and discussed. Comparison between cultivated varieties is made, and morphological characters are described. The line received the name IAPAR 4 Paraná 1" and is recommended in the State for areas with clay soils and free from wilt.